Radiofrequency energy ablation in a child with an implanted vagus nerve stimulator. (20th January 2015) - Radolec, Mackenzy M.; Beerman, Lee B.; Arora, Gaurav
Abstract An 8-year-old girl with supraventricular tachycardia and an implanted vagus nerve stimulator underwent radiofrequency ablation of her supraventricular tachycardia substrate. No known literature exists addressing the potential interaction of these two technologies, although there are reported cases of interaction between radiofrequency and other implanted stimulating devices such as pacemakers. The procedure was performed successfully without observed interaction, and the patient's family reported no significant change in frequency of seizure control.